SiO2 composite aerogel adsorbent as well as preparation method and application thereof

By depositing metal salts on SiO2 aerogel adsorbents prepared by depositing metal salts on SiO2 aerogels, the problems of poor temperature resistance of existing adsorbents and the inability of efficient removal of boron and phosphorus impurities in conventional distillation processes are solved, and efficient and safe polycrystalline silicon impurity removal effect is achieved.

CN119500058APending Publication Date: 2025-02-25GCL NEW (SHANGHAI) PHOTOVOLTAIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411841420.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing adsorbents have poor temperature resistance during the polycrystalline silicon production process, which can easily lead to safety accidents, and conventional distillation processes cannot efficiently remove boron and phosphorus impurities in chlorosilane.

Method used

SiO2 composite aerogel adsorbent is used, which prepares a high temperature resistant, safe and reliable adsorbent by depositing metal salts on SiO2 aerogel, and combines distillation technology to remove boron and phosphorus impurities in chlorosilane.

Benefits of technology

It has achieved efficient removal of boron and phosphorus impurities in chlorosilane, improved the purity of polycrystalline silicon, reduced production costs, and avoided the occurrence of safety accidents.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a SiO2 composite aerogel adsorbent and a preparation method and application thereof.The preparation method of the SiO2 composite aerogel adsorbent comprises the following steps that S1, silica fume is added into a NaOH solution to be stirred, and sodium silicate supernate is taken out after a reaction; s2, adding an acid solution into the sodium silicate supernate, and reacting to obtain SiO2 hydrogel; and S3, dipping the SiO2 hydrogel in a metal salt solution, and then drying the SiO2 hydrogel deposited with the metal salt to obtain the SiO2 composite aerogel. The silica fume is adopted as a raw material to generate SiO2 hydrogel, metal salt is deposited on the SiO2 hydrogel, and the obtained SiO2 composite aerogel can be used for adsorbing boron and phosphorus impurities in chlorosilane based on the super-strong adsorption capacity of SiO2 aerogel and the metal salt deposited on the SiO2 aerogel, and has a relatively strong adsorption effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polysilicon production, and in particular to a SiO2 composite aerogel adsorbent and a preparation method and application thereof. Background Art

[0002] In the process of producing polysilicon, chlorosilane is the main raw material, and the impurities it contains have always been the focus of attention in the industry. Among them, non-metallic impurities mainly include boron, phosphorus, carbon and other elements. Since the segregation coefficient of boron and phosphorus impurities is close to that of chlorosilane, conventional distillation processes cannot achieve efficient removal of boron and phosphorus impurities. The residual boron and phosphorus impurities in polysilicon will act as recombination centers to reduce the minority carrier lifetime, seriously restricting the conversion efficiency of solar cells.

[0003] Multi-stage distillation technology is currently the main technology in the industry for removing impurities from chlorosilanes. However, due to the high energy consumption and large investment of this technology, it will cause a certain degree of pressure on the operation and production of enterprises. Especially in the context of the development of the dual-carbon era, high-energy consumption technology has restricted the sustainable development of enterprises to a certain extent. In order to solve the problem of boron and phosphorus impurities in chlorosilanes, it is proposed to purify chlorosilanes by combining distillation technology with adsorption technology, and the core of this technology is the selection of adsorbents.

[0004] Existing adsorbents are mainly organic matter with poor temperature resistance. They are prone to temperature fluctuations during use, leading to safety accidents. Summary of the invention

[0005] The purpose of the present application is to provide a SiO2 composite aerogel adsorbent and a preparation method and application thereof. The preparation method of the SiO2 composite aerogel adsorbent deposits metal salts on SiO2 aerogel, which solves the problem that the adsorbent in the prior art has poor temperature resistance and is prone to cause safety accidents.

[0006] In order to achieve one of the above-mentioned purposes of the invention, an embodiment of the present application provides a method for preparing a SiO2 composite aerogel adsorbent, comprising the following steps:

[0007] S1: Add microsilica powder into NaOH solution and stir, and take out the sodium silicate supernatant after the reaction;

[0008] S2: adding an acid solution to the sodium silicate supernatant and reacting to obtain SiO2 hydrogel;

[0009] S3: immersing the SiO2 hydrogel in a metal salt solution, and then drying the SiO2 hydrogel with the metal salt deposited thereon to obtain a SiO2 composite aerogel.

[0010] As a further improvement of an embodiment of the present application, in step S1, the solid-liquid weight ratio of the microsilica powder to the NaOH solution is 1:(1-10), and the concentration of the NaOH solution is 2-10wt%.

[0011] As a further improvement of an embodiment of the present application, in step S1, the microsilica powder and the NaOH solution are reacted at a temperature of 100 to 300° C. for 60 to 180 minutes.

[0012] As a further improvement of an embodiment of the present application, in step S2, the acid solution is a H3PO4 solution with a concentration of 3-8 mol / L, and after adding the H3PO4 solution, the pH value of the solution is adjusted to 1-4, and the reaction is carried out for 30-60 minutes.

[0013] As a further improvement of one embodiment of the present application, in step S2, an alkaline solution is added to the solution in which the SiO2 hydrogel is generated to adjust the pH value to 5-6, the solution is allowed to stand, and the SiO2 hydrogel is taken out and washed.

[0014] As a further improvement of an embodiment of the present application, in step S2, the alkaline solution is 1-5 mol / L ammonia water, and after adding ammonia water, it is allowed to stand at a temperature of 40-80° C. for 6-24 hours.

[0015] As a further improvement of an embodiment of the present application, before step S1, a step S0 of pre-treating the microsilica powder is also included, wherein:

[0016] S0: Calcine the microsilica powder at 800-1000°C for 3-6 hours, add the calcined microsilica powder into an acid solution and stir to react, then wash to neutrality and dry.

[0017] As a further improvement of one embodiment of the present application, the acid solution in step S0 is an HCl solution with a concentration of 0.5 to 2 mol / L, and the microsilica powder is added to the HCl solution and magnetically stirred for 4 to 6 hours.

[0018] As a further improvement of an embodiment of the present application, in step S3, the metal salt solution is prepared by dissolving one or more of copper acetate, copper chloride, zinc chloride, cobalt chloride, and manganese chloride in water, and the concentration is 2 to 8 mol / L.

[0019] One embodiment of the present application also provides a SiO2 composite aerogel adsorbent, using SiO2 aerogel as a carrier, and the carrier is loaded with a metal salt, wherein the metal salt is selected from one or more of copper acetate, copper chloride, zinc chloride, cobalt chloride, and manganese chloride.

[0020] One embodiment of the present application also provides an application of the SiO2 composite aerogel adsorbent as described above, wherein the SiO2 composite aerogel adsorbent is used to adsorb boron and phosphorus impurities in chlorosilane.

[0021] One or more technical solutions provided by this application have at least the following technical effects or advantages:

[0022] In the preparation method of the SiO2 composite aerogel adsorbent provided in the present application, waste microsilica powder generated in the industrial silicon smelting process is reacted with NaOH to produce sodium silicate, and an acid solution and an alkaline solution are sequentially added to the sodium silicate supernatant to obtain a SiO2 hydrogel. The SiO2 hydrogel is immersed in a metal salt solution to deposit the metal salt on the SiO2 hydrogel. After drying, the SiO2 composite aerogel is obtained, which can be used to adsorb boron and phosphorus impurities in chlorosilane. DETAILED DESCRIPTION

[0023] The present invention will be described in detail below in conjunction with specific embodiments, but these embodiments do not limit the present invention, and changes in reaction conditions, reactants or raw material amounts made by ordinary technicians in the field according to these embodiments are all included in the protection scope of the present invention.

[0024] The present invention provides a method for preparing a SiO2 composite aerogel adsorbent, comprising the following steps:

[0025] S1: Add microsilica powder into NaOH solution and stir, and take out the sodium silicate supernatant after the reaction;

[0026] S2: adding an acid solution to the sodium silicate supernatant and reacting to obtain SiO2 hydrogel;

[0027] S3: immersing the SiO2 hydrogel in a metal salt solution, and then drying the SiO2 hydrogel with the metal salt deposited thereon to obtain a SiO2 composite aerogel.

[0028] In the present application, waste microsilica powder generated during the industrial silicon smelting process is used as raw material, which can reuse the waste, not only solving the problem of silicon smelting waste treatment, but also reducing the production cost of SiO2 composite aerogel.

[0029] The main component of microsilica powder is SiO2. SiO2 reacts with NaOH to form sodium silicate. Impurities or unreacted SiO2 precipitate at the bottom. Sodium silicate dissolves in water to form sodium silicate supernatant. Take out the sodium silicate supernatant and put it into a clean container. The sodium silicate solution is alkaline. After adding acid solution, sodium silicate will react with acid to form a precipitate to precipitate amorphous SiO2 hydrogel.

[0030] The SiO2 hydrogel is immersed in a metal salt solution to deposit the metal salt on the SiO2 hydrogel, and the SiO2 hydrogel with the metal salt deposited thereon is dried to obtain the SiO2 composite aerogel, wherein the drying method may include supercritical CO2 drying or freeze drying.

[0031] SiO2 aerogel itself has super strong adsorption capacity and can effectively adsorb impurities such as boron and phosphorus in chlorosilane. The metal ions loaded on it can further enhance its ability to remove phosphorus impurities in chlorosilane.

[0032] In some embodiments, step S0 of pretreating the microsilica powder is also included before step S1, wherein S0: calcining the microsilica powder at 800-1000°C for 3-6 hours, adding the calcined microsilica powder into an acid solution and stirring to react, then washing to neutrality and drying.

[0033] In addition to SiO2, microsilica fume also contains impurities such as Fe2O3, Al2O3, CaO, K2O, Na2O, MgO, and C. High-temperature calcination can oxidize C and produce CO2 gas, which is removed from the microsilica fume.

[0034] After removing C impurities, there are still some metal impurities in the micro-silicon powder. When the micro-silicon powder is added to the acid solution, the metal impurities react with the acid and are washed away together with the acid. After drying, high-purity SiO2 micro-silicon powder is obtained. The stirring method can be magnetic stirring, mechanical stirring, etc.

[0035] In some embodiments, the acid solution in step S0 is a HCl solution with a concentration of 0.5 to 2 mol / L, and the microsilica powder is added to the HCl solution and magnetically stirred for 4 to 6 hours. After the microsilica powder reacts with the HCl solution, it is washed to the center with deionized water and dried in a vacuum drying oven.

[0036] Of course, other acid solutions may also be used. HCl is a strong acid, and most metal salts can react with HCl to form water-soluble salts, which can be washed away by water during washing. Even if other acids that can produce precipitation with metal ions are used, the SiO2 hydrogel produced in step S2 is inconsistent with the metal salt precipitation state, and the metal salt precipitation can also be washed away by water in step S2.

[0037] In some embodiments, in step S1, the solid-liquid weight ratio of microsilica powder to NaOH solution is 1:(1-10), and the concentration of NaOH solution is 2-10wt%.

[0038] When SiO2 in microsilica powder reacts with NaOH, under the aforementioned weight ratio of microsilica powder to NaOH solution, NaOH will react completely, and SiO2 will remain as a precipitate. The sodium silicate supernatant can be taken out by standing or centrifugal separation. Using a relatively small amount of NaOH to make NaOH react completely, rather than using a small amount of SiO2 to make SiO2 react completely, can avoid the remaining NaOH solution and the sodium silicate dissolved in water from mixing, which is not conducive to separation.

[0039] In some embodiments, in step S1, the microsilica powder reacts with the NaOH solution at a temperature of 100 to 300° C. for 60 to 180 minutes. Heating during the reaction of SiO2 and NaOH can promote the occurrence of the reaction and accelerate the reaction efficiency of the two.

[0040] In some embodiments, in step S2, the acid solution is a H3PO4 solution with a concentration of 3-8 mol / L. After adding the H3PO4 solution, the pH value of the solution is adjusted to 1-4 and the reaction is carried out for 30-60 minutes.

[0041] In some embodiments, in step S2, an alkaline solution is added to the solution in which the SiO2 hydrogel is generated to adjust the pH value to 5-6, and the solution is allowed to stand, and the SiO2 hydrogel is taken out and washed. The alkaline solution is added to the container to make the solution weakly acidic, and the SiO2 hydrogel is allowed to stand to enhance the structure. Then, the SiO2 hydrogel with enhanced structure is taken out and the Na + Impurity ions such as iodine and sodium iodine are removed to obtain clean SiO2 hydrogel.

[0042] In some embodiments, in step S2, the alkaline solution is 1-5 mol / L ammonia water, and after adding ammonia water, it is allowed to stand at a temperature of 40-80° C. for 6-24 hours.

[0043] Of course, other acids and bases may also be used in step S2 and the acid solution and the base solution in step S2.

[0044] In some embodiments, in step S3, the metal salt solution is prepared by dissolving one or more of copper acetate, copper chloride, zinc chloride, cobalt chloride, and manganese chloride in water, with a concentration of 2 to 8 mol / L. The immersion time is 6 to 24 hours, and a higher concentration of metal salt solution and a longer immersion time are used to deposit as much metal salt as possible on the SiO2 hydrogel, thereby improving the ability to adsorb phosphorus impurities.

[0045] The embodiment of the present application also provides a SiO2 composite aerogel adsorbent, which uses SiO2 aerogel as a carrier, and the carrier is loaded with a metal salt, wherein the metal salt is selected from one or more of copper acetate, copper chloride, zinc chloride, cobalt chloride, and manganese chloride.

[0046] The large specific surface area of ​​SiO2 aerogel gives it super strong adsorption capacity, and its inorganic skeleton makes it resistant to high temperatures and non-flammable. The metal salt can adsorb phosphorus impurities in chlorosilane.

[0047] The present application also provides an application of the SiO2 composite aerogel adsorbent as described above, and the SiO2 composite aerogel adsorbent is used to adsorb boron and phosphorus impurities in chlorosilane. SiO2 aerogel itself has a strong adsorption capacity and can effectively adsorb impurities such as boron and phosphorus in chlorosilane, and metal ions are loaded on it, which can further enhance its ability to remove phosphorus impurities in chlorosilane.

[0048] The technical solution of the present application is further described below in conjunction with some specific embodiments.

[0049] Example 1

[0050] S0: Weigh 20g of microsilica powder and calcine it at 800℃ for 3h; add the calcined microsilica powder into 1mol / L HCl solution for acid washing, react for 4h under magnetic stirring, then wash to the center with deionized water and dry in a vacuum drying oven.

[0051] S1: Weigh 10 g of calcined and acid-washed microsilica powder and 100 g of a 2 wt% NaOH solution, add the microsilica powder into the NaOH solution, heat to 100°C, react for 60 minutes under stirring, and then take out the sodium silicate supernatant by centrifugation.

[0052] S2: 50 ml of sodium silicate supernatant was added with 3 mol / L H3PO4 solution, the pH was adjusted to 1, and the reaction was carried out for 30 min to obtain SiO2 hydrogel. Ammonia water with a concentration of 2 mol / L was added to the solution with SiO2 hydrogel, the pH was adjusted to 5, and the solution was allowed to stand at 40°C for 6 h, and the SiO2 hydrogel was taken out and washed.

[0053] S3: The SiO2 hydrogel is immersed in a copper chloride solution with a concentration of 2 mol / L for 6 hours, and then dried by supercritical CO2 to obtain a SiO2 composite aerogel. The product SiO2 composite aerogel is accumulated through multiple experiments until the amount of SiO2 composite aerogel is sufficient for adsorption experiments.

[0054] The SiO2 composite aerogel synthesized above is used to adsorb and remove boron and phosphorus impurities in chlorosilane. The experimental method is as follows:

[0055] Before adsorption, the SiO2 composite aerogels were dried at 150 °C for 4 h.

[0056] Weigh 5g of the prepared SiO2 composite aerogel and add it to 100ml of chlorosilane solution. Seal the solution containing the SiO2 composite aerogel in a 100mL square-mouthed bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of the SiO2 composite aerogel for boron impurities is 85%, and the removal rate of phosphorus impurities is 95%.

[0057] Example 2

[0058] S0: Weigh 20g of microsilica powder and calcine it at 800℃ for 3h; add the calcined microsilica powder into 1mol / L HCl solution for acid washing, react for 4h under magnetic stirring, then wash to the center with deionized water and dry in a vacuum drying oven.

[0059] S1: Weigh 10 g of calcined and acid-washed microsilica powder and 100 g of a 2 wt% NaOH solution, add the microsilica powder into the NaOH solution, heat to 100°C, react for 60 minutes under stirring, and then take out the sodium silicate supernatant by centrifugation.

[0060] S2: 50 ml of sodium silicate supernatant was added with 3 mol / L H3PO4 solution, the pH was adjusted to 1, and the reaction was carried out for 30 min to obtain SiO2 hydrogel. Ammonia water with a concentration of 2 mol / L was added to the solution with SiO2 hydrogel, the pH was adjusted to 5, and the solution was allowed to stand at 40°C for 6 h, and the SiO2 hydrogel was taken out and washed.

[0061] S3: The SiO2 hydrogel is immersed in a copper acetate solution with a concentration of 2 mol / L for 6 hours, and then dried by supercritical CO2 to obtain a SiO2 composite aerogel. The product SiO2 composite aerogel is accumulated through multiple experiments until the amount of SiO2 composite aerogel is sufficient for adsorption experiments.

[0062] The SiO2 composite aerogel synthesized above is used to adsorb and remove boron and phosphorus impurities in chlorosilane. The experimental method is as follows:

[0063] Before adsorption, the SiO2 composite aerogels were dried at 150 °C for 4 h.

[0064] Weigh 5g of the prepared SiO2 composite aerogel and add it to 100ml of chlorosilane solution. Seal the solution containing the SiO2 composite aerogel in a 100mL square-mouthed bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of the SiO2 composite aerogel for boron impurities is 85%, and the removal rate of phosphorus impurities is 84%.

[0065] Example 3

[0066] S0: Weigh 20g of microsilica powder and calcine it at 800℃ for 4h; add the calcined microsilica powder into 1mol / L HCl solution for acid washing, react for 4h under magnetic stirring, then wash to the center with deionized water and dry in a vacuum drying oven.

[0067] S1: Weigh 10 g of calcined and acid-washed microsilica powder and 100 g of a 2 wt% NaOH solution, add the microsilica powder into the NaOH solution, heat to 100°C, react for 60 minutes under stirring, and then take out the sodium silicate supernatant by centrifugation.

[0068] S2: 50 ml of sodium silicate supernatant was added with 3 mol / L H3PO4 solution, the pH was adjusted to 1, and the reaction was carried out for 30 min to obtain SiO2 hydrogel. Ammonia water with a concentration of 2 mol / L was added to the solution with SiO2 hydrogel, the pH was adjusted to 5, and the solution was allowed to stand at 40°C for 6 h, and the SiO2 hydrogel was taken out and washed.

[0069] S3: The SiO2 hydrogel is immersed in a cobalt chloride solution with a concentration of 2 mol / L for 6 hours, and then dried by supercritical CO2 to obtain a SiO2 composite aerogel. The product SiO2 composite aerogel is accumulated through multiple experiments until the amount of SiO2 composite aerogel is sufficient for adsorption experiments.

[0070] The SiO2 composite aerogel synthesized above is used to adsorb and remove boron and phosphorus impurities in chlorosilane. The experimental method is as follows:

[0071] Before adsorption, the SiO2 composite aerogels were dried at 150 °C for 4 h.

[0072] Weigh 5g of the prepared SiO2 composite aerogel and add it to 100ml of chlorosilane solution. Seal the solution containing the SiO2 composite aerogel in a 100mL square-mouthed bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of the SiO2 composite aerogel for boron impurities is 84%, and the removal rate of phosphorus impurities is 78%.

[0073] Example 4

[0074] S0: Weigh 20g of microsilica powder and calcine it at 800℃ for 4h; add the calcined microsilica powder into 1mol / L HCl solution for acid washing, react for 4h under magnetic stirring, then wash to the center with deionized water and dry in a vacuum drying oven.

[0075] S1: Weigh 10 g of calcined and acid-washed microsilica powder and 100 g of a 6 wt% NaOH solution, add the microsilica powder into the NaOH solution, heat to 100°C, react for 60 minutes under stirring, and then take out the sodium silicate supernatant by centrifugation.

[0076] S2: 50 ml of sodium silicate supernatant was added with 3 mol / L H3PO4 solution, the pH was adjusted to 1, and the reaction was carried out for 30 min to obtain SiO2 hydrogel. Ammonia water with a concentration of 2 mol / L was added to the solution with SiO2 hydrogel, the pH was adjusted to 5, and the solution was allowed to stand at 40°C for 6 h, and the SiO2 hydrogel was taken out and washed.

[0077] S3: The SiO2 hydrogel is immersed in a copper chloride solution with a concentration of 2 mol / L for 6 hours, and then dried by supercritical CO2 to obtain a SiO2 composite aerogel. The product SiO2 composite aerogel is accumulated through multiple experiments until the amount of SiO2 composite aerogel is sufficient for adsorption experiments.

[0078] The SiO2 composite aerogel synthesized above is used to adsorb and remove boron and phosphorus impurities in chlorosilane. The experimental method is as follows:

[0079] Before adsorption, the adsorbent was dried at 150 °C for 4 h.

[0080] Weigh 5g of the prepared SiO2 composite aerogel and add it to 100ml of chlorosilane solution. Seal the solution containing the SiO2 composite aerogel in a 100mL square-mouthed bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of the SiO2 composite aerogel for boron impurities is 96%, and the removal rate of phosphorus impurities is 95%.

[0081] Example 5

[0082] S0: Weigh 20g of microsilica powder and calcine it at 800℃ for 4h; add the calcined microsilica powder into 1mol / L HCl solution for acid washing, react for 4h under magnetic stirring, then wash to the center with deionized water and dry in a vacuum drying oven.

[0083] S1: Weigh 10 g of calcined and acid-washed microsilica powder and 100 g of a 10 wt% NaOH solution, add the microsilica powder into the NaOH solution, heat to 100°C, react for 60 minutes under stirring, and then take out the sodium silicate supernatant by centrifugation.

[0084] S2: 50 ml of sodium silicate supernatant was added with 3 mol / L H3PO4 solution, the pH was adjusted to 1, and the reaction was carried out for 30 min to obtain SiO2 hydrogel. Ammonia water with a concentration of 2 mol / L was added to the solution with SiO2 hydrogel, the pH was adjusted to 5, and the solution was allowed to stand at 40°C for 6 h, and the SiO2 hydrogel was taken out and washed.

[0085] S3: The SiO2 hydrogel is immersed in a copper chloride solution with a concentration of 2 mol / L for 6 hours, and then dried by supercritical CO2 to obtain a SiO2 composite aerogel. The product SiO2 composite aerogel is accumulated through multiple experiments until the amount of SiO2 composite aerogel is sufficient for adsorption experiments.

[0086] The SiO2 composite aerogel synthesized above is used to adsorb and remove boron and phosphorus impurities in chlorosilane. The experimental method is as follows:

[0087] Before adsorption, the adsorbent was dried at 150 °C for 4 h.

[0088] Weigh 5g of the prepared SiO2 composite aerogel and add it to 100ml of chlorosilane solution. Seal the solution containing the SiO2 composite aerogel in a 100mL square-mouthed bottle with a lid, and then oscillate at a constant temperature for 2 hours. After adsorption equilibrium, take the mixed solution for ICP test. The results show that the removal rate of the SiO2 composite aerogel for boron impurities is 90%, and the removal rate of phosphorus impurities is 95%.

[0089] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0090] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing a SiO2 composite aerogel adsorbent, characterized in that: The steps include: S1: Add microsilica powder into NaOH solution and stir, and take out the sodium silicate supernatant after the reaction; S2: adding an acid solution to the sodium silicate supernatant and reacting to obtain SiO2 hydrogel; S3: immersing the SiO2 hydrogel in a metal salt solution, and then drying the SiO2 hydrogel with the metal salt deposited thereon to obtain a SiO2 composite aerogel.

2. The method for preparing the SiO2 composite aerogel adsorbent according to claim 1, characterized in that: In step S1, the solid-liquid weight ratio of the microsilica powder to the NaOH solution is 1:(1-10), and the concentration of the NaOH solution is 2-10wt%.

3. The method for preparing the SiO2 composite aerogel adsorbent according to claim 2, characterized in that: In step S1, the microsilica powder and the NaOH solution are reacted at a temperature of 100 to 300° C. for 60 to 180 minutes.

4. The method for preparing the SiO2 composite aerogel adsorbent according to claim 1, characterized in that: In step S2, the acid solution is a H3PO4 solution with a concentration of 3-8 mol / L. After adding the H3PO4 solution, the pH value of the solution is adjusted to 1-4, and the reaction is carried out for 30-60 minutes.

5. The method for preparing the SiO2 composite aerogel adsorbent according to claim 4, characterized in that: In step S2, an alkaline solution is added to the solution in which the SiO2 hydrogel is generated to adjust the pH value to 5-6, and the solution is allowed to stand, and the SiO2 hydrogel is taken out and washed.

6. The method for preparing the SiO2 composite aerogel adsorbent according to claim 5, characterized in that: In step S2, the alkaline solution is 1-5 mol / L ammonia water, and after adding ammonia water, the mixture is allowed to stand at 40-80° C. for 6-24 hours.

7. The method for preparing the SiO2 composite aerogel adsorbent according to claim 1, characterized in that: Before step S1, step S0 of pre-treating the microsilica powder is also included, wherein: S0: Calcine the microsilica powder at 800-1000°C for 3-6 hours, add the calcined microsilica powder into an acid solution and stir to react, then wash to neutrality and dry.

8. The method for preparing the SiO2 composite aerogel adsorbent according to claim 7, characterized in that: The acid solution in step S0 is a HCl solution with a concentration of 0.5 to 2 mol / L. After the microsilica powder is added to the HCl solution, magnetic stirring is performed for 4 to 6 hours.

9. The method for preparing the SiO2 composite aerogel adsorbent according to claim 1, characterized in that: In step S3, the metal salt solution is prepared by dissolving one or more of copper acetate, copper chloride, zinc chloride, cobalt chloride and manganese chloride in water, and the concentration is 2-8 mol / L.

10. A SiO2 composite aerogel adsorbent, characterized in that: SiO2 aerogel is used as a carrier, and a metal salt is loaded on the carrier, wherein the metal salt is selected from one or more of copper acetate, copper chloride, zinc chloride, cobalt chloride and manganese chloride.

11. The use of SiO2 composite aerogel adsorbent as claimed in claim 10, characterized in that: The SiO2 composite aerogel adsorbent is used for adsorbing boron and phosphorus impurities in chlorosilane.